Malpractice in Radiology: What Should You Worry About? - Alessandro Cannavale; Mariangela Santoni; Paola Mancarella; Roberto Passariello; Paolo Arbarello (Radiology Research and Practice)
Over recent years the professional role of the radiologist has been evolved due to the increasing involvement in the clinical management of the patient. Radiologists have thus been increasingly charged by new duties and liabilities, exposing them to higher risks of legal claims made against them. Malpractice lawsuits in radiology are commonly related to inappropriate medical care or to the poor physician-patient relationship. In the present paper, we provide overview of the basic principles of the medical malpractice law and the main legal issues and causes of legal actions against diagnostic and interventional radiologists. We also address some issues to help radiologists to reduce risks and consequences of malpractice lawsuits. These include (1) following the standard of care to the best of their ability, (2) cautious use of off-label devices, (3) better communication skills among healthcare workers and with the patient, and (4) ensuring being covered by adequate malpractice insurance. Lastly, we described definitions of some medicolegal terms and concepts that are thought to be useful for radiologists to know.